Pengaruh Media Ular Tangga Terhadap Kemampuan Berbicara Siswa Kelas V - putri, siti nabila; Wahid, Aaz Fauzi; Hilaliyah, Tatu (Peneliti.net, 2024)
This study aims to describe and determine the influence of snakes and ladders media on the speaking ability of grade V students. This study uses quasi-experimental methods or quasi-quantitative experiments and design selection in the form of pretest-posttest. This technique uses two different classes. The first class is class V-A as an experimental class in learning using snake and ladder media, while the control class is class V-C using image media as a comparison. The results obtained from the average pretest of 65.33 and posttest of 79.60 saw an increase in the average value of the pretest and posttest which were 2.57 points apart. Then continued the average difference in the final test using a two-party t-test with a significant level (α= 0.05). The result of calculating the value of ttable = 2.002 and tcalculate = 1.391 with the criterion if –ttabel < tcalculate < ttable then Ha is accepted. From the calculation results, it is obtained -2.002 < 1.391 > 2.002, so it is in accordance with the test criteria -ttable < tcalculate > ttable. So Ho accepted Ha was rejected. That is, there is no significant influence between the use of snakes and ladders media and image media, but snakes and ladders media have an effect on the speaking ability of grade V students.